Textos multimodais no ensino de língua portuguesa: práticas de leitura e produção escrita no contexto digital - Morello, Renata Viebrantz (2024)
With the emergence of new technologies, the practice of reading and writing began to demand from people a set of additional knowledge to understand new modalities presented in texts, especially in the digital context. In various aspects of our lives, both professional and social, the form of communication and interaction is conducted through different languages. As a result, there is a significant demand in schools to train students with different reading, interpretation and writing skills. In this constantly evolving scenario, to promote effective understanding and production, it is essential that reading and writing practices include multimodal texts, which combine verbal and visual languages. Reading should provide a critical and reflective perspective, enabling individuals to use it ethically and democratically in their lives. In this sense, we chose as the theme of this research reading, interpretation and textual production from the perspective of multiliteracies in multimodal texts, in order to contribute to the formation of multiliterate students through interactive practices and procedures in the digital context. The general objective is to develop reading practices aimed at interpretation and written production by students in the 2nd year of high school in a federal public institution, in a Portuguese language teaching situation, through the use of multimodal texts based on the perspective of students. multiliteracies, including digital interactive approaches. In view of the above, the following theoretical foundations are articulated: Antunes (2003), Bakhtin (2016), document from the National Common Curricular Base (Brazil, 2018), Fiorin (2016), Kleiman (2002), Lopes-Rossi (2011), Marcuschi (2008), Petit (2008) and Rojo (2009) regarding reading practices and speech genres; Dionísio (2011), Pimenta (2006) Kress (2003), Kress and van Leeuwen (2021), Rojo (2009, 2012) and van Leeuwen (2017) about discursive multimodality; Cazden et al. (2021), Kalantzis, Cope and Pinheiro (2020), Heberle (2012) and Rojo (2012) in relation to multiliteracies; Coscarelli and Ribeiro (2021), Knobel and Lankshear (2006, 2008) and Lemke (2010) regarding digital literacies. As for the methodology, it uses an applied, exploratory and bibliographical research developed through action research, with a qualitative approach, carried out in a 2nd year class of integrated high school, at a federal public school, in the city of Passo Fundo (RS). The main corpus used throughout the research comprises the discursive genre "advertising" with a focus on the environment and sustainability. The research results emphasize that the practices of reading, interpretation and textual production with multimodal discursive genres, facilitated through digital interactive procedures, promote an interactive and engaging approach on the part of students. This translates into notable interest, engagement and learning in the proposed activities. Since the school institution must ensure that students have access to technologies and opportunities to develop their reading skills for comprehension and written production in the context of teaching the Portuguese language, which can contribute to a social transformation that is both possible and necessary, preparing students to meaningfully exercise their citizenship.